Examining alcohol use disorder treatment utilization in lesbian, gay, and bisexual populations through the Behavioral Model for Vulnerable Populations - Micale, Anthony M. (Journal of addictions & offender counseling, 2025)
There is significant need for alcohol use disorder (AUD) treatment among lesbian, gay, and bisexual (LGB) individuals. Furthermore, utilization among LGB individuals is below indicated treatment need due to interpersonal and structural barriers. A hierarchical logistic regression examined relationships among perceived public, interpersonal, and healthcare discrimination in relation to treatment utilization using secondary data from a subsample of the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III. Findings indicate that increased public and interpersonal discrimination is associated with higher likelihood of healthcare discrimination. Healthcare discrimination predicted higher AUD treatment use. Clinical implications and recommendations for future research are discussed.